Exploring the Relationship Between Cultural Capital and University EFL Students’ Speaking Performance - Fara Desi Puspitasari; Pornchanit Chaiyalerd (New Language Dimensions, 2025)
Cultural capital has been widely discussed in Bourdieu’s theory as a factor that influences students’ academic experiences, including language learning. In the EFL context, the diversity of cultural capital types owned by students may affect their speaking performance in different ways. Therefore, this study aimed to identify the types of cultural capital possessed by EFL university students, examine the relationship between cultural capital diversity and students’ speaking performance, and find out which aspects of cultural capital have the strongest influence on speaking performance at the university level. This study used a quantitative correlational design and involved 44 English Education students from a public university in Surabaya. Data on cultural capital were collected through a questionnaire consisting of seven cultural capital factors, while students’ speaking performance was taken from the final scores of Public Speaking and Academic Speaking courses. The data were analyzed using descriptive statistics and Pearson product–moment correlation. The results showed that most students had medium to high levels of cultural capital diversity, with art appreciation, cultural visits, and cultured family as the dominant factors. The students’ speaking performance was also mostly in the medium to high category. In addition, the analysis showed a significant medium positive correlation between cultural capital diversity and speaking performance (r = .411; p < .01), which means that students with higher cultural capital diversity tended to have better speaking performance. These findings suggest that cultural capital plays a role in supporting students’ speaking development in the EFL university context.